2020
DOI: 10.3390/en13164224
|View full text |Cite
|
Sign up to set email alerts
|

Solar Photovoltaic Tracking Systems for Electricity Generation: A Review

Abstract: This paper presents a thorough review of state-of-the-art research and literature in the field of photovoltaic tracking systems for the production of electrical energy. A review of the literature is performed mainly for the field of solar photovoltaic tracking systems, which gives this paper the necessary foundation. Solar systems can be roughly divided into three fields: the generation of thermal energy (solar collectors), the generation of electrical energy (photovoltaic systems), and the generation of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 97 publications
(77 reference statements)
0
42
0
2
Order By: Relevance
“…At the same time, solar radiation can also be converted to electricity using solar power systems. Solar systems are classified into two types: photovoltaic (PV) systems that convert sunlight directly to electricity using semiconductor materials [36,[76][77][78][79] and concentrated solar power (CSP) systems that convert sunlight to heat before using the heat to produce electricity [30,41,46,51,80]. Despite the fact that both processes need solar radiation to occur, the photosynthesis process is concerned more with the Photosynthesis Active Radiation (PAR) range [47,52,68,[81][82][83] while electrical energy generation is dependent on solar irradiance or light intensity [8,15,35,84,85].…”
Section: The Importance Of Solar Radiation For Energy Generation and Crop Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, solar radiation can also be converted to electricity using solar power systems. Solar systems are classified into two types: photovoltaic (PV) systems that convert sunlight directly to electricity using semiconductor materials [36,[76][77][78][79] and concentrated solar power (CSP) systems that convert sunlight to heat before using the heat to produce electricity [30,41,46,51,80]. Despite the fact that both processes need solar radiation to occur, the photosynthesis process is concerned more with the Photosynthesis Active Radiation (PAR) range [47,52,68,[81][82][83] while electrical energy generation is dependent on solar irradiance or light intensity [8,15,35,84,85].…”
Section: The Importance Of Solar Radiation For Energy Generation and Crop Cultivationmentioning
confidence: 99%
“…This total solar irradiance is referred to as solar irradiation. The amount and intensity of R s that the earth's surface receives depends on a variety of factors such as cloud cover [81,[90][91][92][93], latitude [6,73,80,94], altitude [77,78,90,95], season [73,93,[96][97][98], weather [19,38,40,99,100], and daytime [34,46,48,76,101]. In addition, the distance that radiation has to travel is dependent on the angle of the sun [88,93].…”
Section: Light Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the research has brought new concepts and tested new solutions, which can be found in the paper of Seme that presents an updated scenario [2]. The manufacturers have also continued to develop their technologies, each one with its specific tracking error, that is, the deviation of the angle between the sun ray and the normal of the photovoltaic panel, which should be as low as possible as a function of the chosen geometry and electromechanical parts involved.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Zhang, for instance, used photodiodes in a dual-axis hybrid solar track system, which also uses a GPS module [5]. As another more recent alternative, the inclinometer, a device designed to measure the angle of an object with respect to the force of gravity, also called the tilt sensor, has been used in order to adjust the position of the PV panels adopted according to the model and geometry adopted [2].…”
Section: Introductionmentioning
confidence: 99%